RWP-RK domain-containing transcription factors in the Viridiplantae: biology and phylogenetic relationships. (23rd May 2022) - Sakuraba, Yasuhito; Zhuo, Mengna; Yanagisawa, Shuichi
Abstract: The RWP-RK protein family is a group of transcription factors containing the RWP-RK DNA-binding domain. This domain is an ancient motif that emerged before the establishment of the Viridiplantae—the green plants, consisting of green algae and land plants. The domain is mostly absent in other kingdoms but widely distributed in Viridiplantae. In green algae, a liverwort, and several angiosperms, RWP-RK proteins play essential roles in nitrogen responses and sexual reproduction-associated processes, which are seemingly unrelated phenomena but possibly interdependent in autotrophs. Consistent with related but diversified roles of the RWP-RK proteins in these organisms, the RWP-RK protein family appears to have expanded intensively, but independently, in the algal and land plant lineages. Thus, bryophyte RWP-RK proteins occupy a unique position in the evolutionary process of establishing the RWP-RK protein family. In this review, we summarize current knowledge of the RWP-RK protein family in the Viridiplantae, and discuss the significance of bryophyte RWP-RK proteins in clarifying the relationship between diversification in the RWP-RK protein family and procurement of sophisticated mechanisms for adaptation to the terrestrial environment. Abstract : RWP-RK proteins are widely distributed in Viridiplantae. Studies on bryophyte RWP-RK proteins may help elucidate how nitrogen- and gametogenesis-related regulatory processes evolved into sophisticated systems in land plants.